Gestational weight gain and postpartum weight retention in Tasmanian women: The Baby-bod Study. - Sisitha Jayasinghe; Manoja P Herath; Jeffrey M Beckett; Kiran D K Ahuja; Steven J Street; Nuala M Byrne; Andrew P Hills (PLoS ONE, 2022)
Many factors can negatively impact perinatal outcomes, including inappropriate gestational weight gain (GWG). Despite having the greatest potential to influence maternal and infant health, there is a lack of consensus regarding the GWG consistent with a healthy pregnancy. To date, GWG in Northern Tasmania remains understudied. We investigated how maternal pre-pregnancy body mass index (BMI) is related to weight gain during pregnancy and weight retention post-partum, and how maternal pre-pregnancy BMI is related to the mode of delivery. Approximately 300 Tasmanian mothers (n = 291 for mode of delivery and n = 282 for GWG) were included in this study. Analysis of variance and chi square tests were conducted to assess differences in BW of mothers across BMI categories and differences between categorical variables; respectively. Based on pre-pregnancy BMI, mothers were assigned to one of three groups, with healthy weight (<25 kg m-2), with overweight (25-29.9 kg m-2), or with obesity (>30 kg m-2). Pre-pregnancy BMI and body weight (BW) were significantly associated (p<0.001) with post-partum BW at 3 and 6 months. Only 25% of mothers with a normal weight BMI, 34% with overweight and 13% with obesity, achieved the Institute of Medicine (IOM) recommendation for GWG. Interestingly, a number of women in our cohort lost weight during gestation (1.5, 9 and 37% in <25, 25-29.9 and >30 kg m-2 groups, respectively). Further, women with obesity showed the lowest level of BW fluctuation and retained less weight post-partum. The highest number of caesarean sections were observed in mothers who exceeded GWG recommendations. Most mothers either exceeded or failed to achieve IOM recommendations for GWG. To improve the generalisability of these findings, this study should be replicated in a larger representative sample of the Tasmanian maternal population.